Assessing Students' Creative Thinking With The Implementation of Design Thinking Based Project - Baiq, Fatmawati (Sumber Belajar Sejahtera, 2024)
The focus of this study is to apply design-thinking learning to measure students' creative thinking skills in microbiology courses at universities. The type of pre-experimental research with one group pretest - posttest design. Respondents were 27 student in four semester in the biology education study program, Hamzanwadi University FMIPA. Data collection techniques using Worksheets based project with indicators for design project: problem, solution, objective, and procedure. Data analysis techniques are descriptive quantitative by calculating the gain test of creative thinking skills, the percentage of creative thinking ability categories, and the percentage of fermentation product categories. The creative thinking gain score on the components: posing problems 1.09., proposing solutions 0.88., stating objectives 1.07., and compiling work methods 1.65 with a high category. The percentage of product categories made is general 29.2%, and modification 0.8%, no new fermentation products are produce. Through design thinking, educators can adjust their teaching methods to meet the various learning styles of students, making materials more accessible and relative. By combining real-world problems and practical activities into learning, students are encouraged to think creatively when solving challenges related to microbiology, resulting in creativity in making fermentation products. Design thinking based project learning can measure students' creative thinking skills in microbiology courses, even though at the ideate stage they repeatedly prepare project designs during the learning process and at the prototype stage there is a failure in making fermented products